Training load management in rhythmic gymnastics - Debien, P. B. (Revista Educação em Foco, 2020)
Rhythmic gymnastics is a complex aesthetic sport, which requires perfection of technical gestures, associated with well-developed physical and artistic capacities. Although there is scarce literature, research has shown high training loads and maladaptation occurrence among rhythmic gymnasts. Moreover, there is still a gap between scientific knowledge and practices implemented in the field. Therefore, the general purpose of this thesis was to advance the knowledge surrounding training load management in rhythmic gymnastics. A comprehensive literature review and two studies were developed in this research program. Study one aimed to describe individual training load, recovery and injuries in elite group rhythmic gymnasts during competitive periods. Six gymnasts from the Brazilian senior rhythmic gymnastics group were monitored daily over a 126-day period comprising regular training and four competitions. Training load was measured using the session rating of perceived exertion (session-RPE). Daily load, chronic load, and acute:chronic workload ratio (ACWR) were assessed. The Total Quality Recovery (TQR) scale was used to monitor recovery and a 3-day rolling average (3RA) TQR was also measured. Injuries were diagnosed and reported by the medical staff and their reports were used in the analysis. Descriptive statistics were used. The gymnasts presented distinct daily load, ACWR, and recovery patterns, as well as injuries across the competitive periods. All athletes had rapid increases ("spikes") in load. Three athletes were underrecovered more than 60% of the time. Four athletes sustained five injuries during the time of the study (all lower limb overuse injuries, two severe, two mild, one slight). Individual factors such as age and chronic load could moderate how each gymnast responds to training and tolerates spikes in load. Moreover, injuries sustained during competitive periods appear to affect the short and long-term careers of gymnasts, as well as impair training and competition organization of the team. The purpose of the second study was to describe and analyse the practices and perceptions of rhythmic gymnastics coaches, medical staff, and athletes on training load management. Online surveys were distributed among professionals and gymnasts currently involved in rhythmic gymnastics training across the world. One hundred (N=50 coaches, N=12 medical staff, N=38 gymnasts) participants from 25 different countries completed the surveys. Coaches` perception was frequently used as a method of monitoring load, recovery/fatigue, and performance. Variables, methods, and metrics commonly reported in the training load literature and other sports were not very frequently used in rhythmic gymnastics. The majority of coaches perceived that maladaptation rarely or never occurred. Medical staff involvement in sharing and discussing training load information was limited and they also perceived that the measurement of athletes` recovery/fatigue was not very good. Gymnasts noted good quality on measuring performance and receiving feedback. Most participants believed that a specific training load management model for rhythmic gymnastics could be very or extremely effective. In conclusion, training load management in rhythmic gymnastics needs to move from a coach-centred process focused on technical components to a multidisciplinary approach centred on the gymnasts in order to minimize negative outcomes.